The modeling of how visibility ranges can affect the fire evacuation in modern buildings - Hong, Chang Bin. (2010)
In the past research, wherever an occupant is in the compartment, he is always able to see the exit signs clearly and escape during emergency. This assumption is not realistic when the compartment concerned is filled with smoke. In order to simulate the group behavior of occupants, a rule termed “flow with the stream” is introduced in this final year project. Basically, this rule stipulates that the movement of an individual occupant will be limited byr low visibility conditions and guided by friends and family members who are in groups.